حماية حقوق الطفل في التشريع الجزائري - هانية بركان; هدى رمضاني (My University, 2023)
Summary provision of protection for the child is one of the most important tasks that all countries of the world aim at, and Algeria is among the countries that seek to achieve protection for this group at all levels, as a basic nucleus for building societies and creating an aware generation away from various human rights violations. From this standpoint, Algeria has issued the law No. 115 related to the protection of the rights of the child, as we note on this new law that it regulated all of the social protection of the child through the National Commission for the Protection and Promotion of Childhood under the chairmanship of the National Commissioner for the Protection and Promotion of Childhood, and we do not forget the role played by the means of open media in providing various services to children at risk and help their families. The same law deals with the judicial protection of delinquent children, and we note that the Algerian legislator has allocated special procedures for him that differ from those prescribed for adults, and has also approved guarantees for him to protect him throughout the stages of the course of these procedures. ............................................................................. ملخص : إن توفير الحماية للطفل تعتبر من أكثر المهام التي ترمي إليها كل دول العالموالجزائر من بين الدول التي تسعى إلى تحقيق الحماية لهذه الفئة على جميع المستويات،بإعتباره نواة أساسية لبناء مجتمعات، وخلق جيل واعي بعيدا عن مختلف الإنتهاكاتالحقوقية. ومن هذا المنطلق فلقد أصدرت الجزائر القانون رقم 15-12المتعلق بحماية حقوق الطفل، إذ نلاحظ على هذا القانون المستحدث أنه نظم كل من الحماية الاجتماعية للطفل عن طريق الهيئة الوطنية لحماية وترقية الطفولة تحت رئاسة المفوض الوطني لحماية وترقية الطفولة،كما لا ننسى الدور الذي تلعبه وسائل الوسط المفتوح من تقديم مختلف الخدمات للأطفال في خطر ومساعدة أسرهم. إذ تطرق ذات القانون إلى الحماية القضائية للطفولة الجانحة ونلاحظ أن المشرع الجزائري خصص له إجراءات خاصة تختلف عن تلك المقررة للبالغين، كما أقر له ضمانات تحميه طيلة مراحل سير الإجراءات. ................................................................................ Résumé : La protection de l'enfance est l'une des tâches les plus importantes que tous les pays du monde visent, et l'Algérie fait partie des pays qui cherchent à assurer la protection de ce canal à tous les niveaux, car c'est le noyau du sublime pour la construction des sociétés. Créer une génération consciente loin des diverses violations des droits de l'homme. Dans cette optique, l'Algérie a promulgué la loi n°13 129 relative à la protection des droits de l'enfant, car on note sur cette nouvelle loi qu'elle réglemente l'ensemble de la protection sociale de l'enfant à travers l'Autorité Nationale de Protection et de Promotion de l'Enfance sous la présidence du Commissariat National à la Protection et à la Promotion de l'Enfance, et n'oublions pas le rôle joué par les moyens Le centre ouvert est en mesure d'offrir divers services aux enfants à risque et d'aider leurs familles. Comme la même loi touche à la protection judiciaire de l'enfance pandémique, et note que le législateur algérien lui a alloué des procédures spéciales qui diffèrent de celles prescrites pour les adultes, et lui a également approuvé des garanties pour le protéger tout au long des étapes de son cheminementprocédures.